2021
DOI: 10.1111/cea.13961
|View full text |Cite
|
Sign up to set email alerts
|

Increased epithelial galectin‐13 expression associates with eosinophilic airway inflammation in asthma

Abstract: Background Airway eosinophilic inflammation is a central feature in asthma which is mainly driven by type 2 response. The expression of galectin‐13 was up‐regulated in a parasitic infection model which is also characterized by type 2 immune response. We hypothesized that galectin‐13 may be involved in airway eosinophilic inflammation in asthma. Objective To unveil the role of galectin‐13 in asthma airway inflammation. Methods We measured galectin‐13 expressions in bronchial brushings, sputum, and plasma of ast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 37 publications
(73 reference statements)
0
10
0
Order By: Relevance
“…In addition to pulmonary function parameters, PTPRH protein level in sputum supernatant was not only positively correlated with IL-4, IL-5, IL-13, which were associated with Th2 high asthma, but also associated with SERPINB2 and POSTN, Th2 signature. 22,23 Our study found that treatment with PTPRH relieved HDM challenge-induced airway inflammation and mucus overproduction in asthma model. Inflammation leading to an overproduction of mucus induces airflow obstruction.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…In addition to pulmonary function parameters, PTPRH protein level in sputum supernatant was not only positively correlated with IL-4, IL-5, IL-13, which were associated with Th2 high asthma, but also associated with SERPINB2 and POSTN, Th2 signature. 22,23 Our study found that treatment with PTPRH relieved HDM challenge-induced airway inflammation and mucus overproduction in asthma model. Inflammation leading to an overproduction of mucus induces airflow obstruction.…”
Section: Discussionmentioning
confidence: 69%
“…SERPINB2 and POSTN, is an epithelial gene signature for Th2 high asthma. 22,23 These data indicates that PTPRH involves in asthma featured with Th2 inflammation.…”
Section: Ptprh Protein Levels Were Associated With Th2 High Asthmamentioning
confidence: 74%
“…18 Another study showed that Gal-13, a novel marker of airway eosinophilia in asthma, could lead to increased inflammatory infiltration and apoptosis of allergic airway eosinophils by upregulating MCP-1 and eotaxin-1 expression. 19 In this study, we found that Gal-7 was upregulated in TGF-β1-induced BEAS-2B cells, and was regulated by the upstream transcription factor CTCF to accelerate cell damage. The above findings further clarify the possible regulatory mechanism of Gal-7 in the process of asthma.…”
Section: Ctcf Activated the Jnk/stat3 Axis Through Transcriptional Re...mentioning
confidence: 65%
“…Tian et al found increased bronchial epithelial detachment and apoptosis, airway smooth muscle, and basement membrane thickening in Gal‐7 transgenic (+) mice when treated with respiratory syncytial virus or ovalbumin 18 . Another study showed that Gal‐13, a novel marker of airway eosinophilia in asthma, could lead to increased inflammatory infiltration and apoptosis of allergic airway eosinophils by upregulating MCP‐1 and eotaxin‐1 expression 19 . In this study, we found that Gal‐7 was upregulated in TGF‐β1‐induced BEAS‐2B cells, and was regulated by the upstream transcription factor CTCF to accelerate cell damage.…”
Section: Discussionmentioning
confidence: 99%
“…With the exception of HBB , SERPINB11 , and DPP4 , the trend of other candidate DEGs was consistent between the above two datasets. Candidate DEGs including SERPINB2 , POSTN , and CLCA1 have already been reported to participate in asthma ( 22 ). Among the remaining candidate DEGs, the expressions of two members of the SPRRs family ( SPRR1B and SPRR3 ) were upregulated ( Figures 1B–E ).…”
Section: Resultsmentioning
confidence: 99%